2020
DOI: 10.1002/ca.23655
|View full text |Cite
|
Sign up to set email alerts
|

A review of anatomy education during and after the COVID‐19 pandemic: Revisiting traditional and modern methods to achieve future innovation

Abstract: The coronavirus disease 2019 (COVID‐19) pandemic has had enormous effects on anatomy education. During the pandemic, students have had no access to cadavers, which has been the principal way to learn anatomy since the 17 th century. As it is difficult to predict future access to cadavers for students or in‐person classes, anatomy educators are encouraged to revisit all possible teaching methods in order to develop innovations. Here, we review anatomy education methods to apply to current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
253
0
12

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(266 citation statements)
references
References 80 publications
(102 reference statements)
1
253
0
12
Order By: Relevance
“…With regard to the acquisition of anatomy learning, previous studies have suggested various methods to assist or replace cadaver-based learning. 6,26,27 In contrast, other studies asserted that the experience and knowledge acquired by hands-on cadaver dissection in anatomy laboratories are invaluable. 28,29 In addition, the cadaver dissection laboratory is the space where medical students meet their first patient and this significantly affects students' medical professionalism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the acquisition of anatomy learning, previous studies have suggested various methods to assist or replace cadaver-based learning. 6,26,27 In contrast, other studies asserted that the experience and knowledge acquired by hands-on cadaver dissection in anatomy laboratories are invaluable. 28,29 In addition, the cadaver dissection laboratory is the space where medical students meet their first patient and this significantly affects students' medical professionalism.…”
Section: Discussionmentioning
confidence: 99%
“… 3 4 Anatomy education has been presented with various platforms, with multiple opinions regarding the conducting of online classes, and the sudden conversion to online. 5 6 7 In Korea, anatomy lectures were changed to entirely online at all medical schools, and the dissection laboratories were either replaced virtually or postponed until after the COVID-19 situation improved.…”
Section: Introductionmentioning
confidence: 99%
“…The authors do however make very valid points about the benefits of dissection and the advantages it affords to students, which we unreservedly agree with. Students gain not only anatomical knowledge, but also life lessons in ethics and humanity [2,5]. In light of this, despite the pandemic having and continuing to cause problems with the delivery of medical education, institutions and educators are continuing to seek ways to ensure pedagogies such as dissection are integrated into the modified curriculum.…”
Section: Lettermentioning
confidence: 99%
“…Moving forwards, universities will undoubtedly rely heavily on technologies such as online dissection videos and anatomical lectures. However, dissection is too rich in educational opportunity and benefit for institutions to indefinitely curtail its use as an anatomical pedagogy [2,4,5].…”
Section: Lettermentioning
confidence: 99%
“…[10] used AR with good results to implement real laboratory experiments in the field of materials science to enable students to carry out their experiments from home. [11] showed the advantages of using AR in anatomy education.…”
Section: Introductionmentioning
confidence: 99%